Emissões de gases de efeito estufa no processamento da mandioca: um estudo de mitigação com base em avaliação de ciclo de vida - Bezerra, Julio Cesar Sales (2025)
Cassava (Manihot esculenta Crantz) plays a key role in ensuring food and economic security for small farmers in tropical countries. In this context, the present study aimed to detail the production process of cassava flour, focusing on the quantification of greenhouse gas (GHG) emissions through Life Cycle Assessment (LCA), as well as on the identification of effective strategies to reduce these environmental impacts. To achieve this goal, the study was guided by three specific objectives. The first was to conduct a bibliometric review on the application of LCA to the cassava production chain and its processing into flour. The analysis revealed that only 118 publications were produced between 1981 and 2023 on cassava-related topics, of which only 10 directly addressed the LCA of the cassava production process, indicating a significant gap in scientific knowledge. The second specific objective referred to the execution of the LCA of the cassava flour production process, covering the stages of planting, harvesting, and processing. Two cassava flour mills, referred to as CF-I and CF-II, were analyzed. The LCA results indicated that the emissions associated with the annual production of 2,600 kg of cassava flour were 2,449.28 kg CO2-eq/year for CF-I and 1,027.03 kg CO2-eq/year for CF-II. These differences were due to the type of fossil fuel used for transporting the roots and the type of oven used in the roasting process, which directly affects the amount of firewood consumed. These stages were identified as the main sources of GHG emissions in the two units analyzed. Finally, the third specific objective was related to mitigation strategies. Replacing the fuel used in transportation and adopting a more energy-efficient oven resulted in reductions of 357.49 kg CO2-eq/year in root transportation and 1,672.32 kg CO2-eq/year in the roasting process, corresponding to 90.3% and 60.0% of the original emissions, respectively. The results demonstrate that implementing sustainable practices, even in small-scale units, can significantly reduce emissions without compromising productivity.